THE EFFECT OF SELF-ASSESSMENTAND SELF-CONCEPT ON STUDENTSÃ¢â¬â¢ WRITING COMPETENCY AT EIGHTH GRADE OF MTS DARUL AITAM JEROWARUIN ACADEMIC YEAR 2012/2013 - ., JUMARAH; ., Prof. Dr. A. A. I. Ngurah Marhaeni,MA; ., Prof. Dr. Nyoman Dantes (Jurnal Pendidikan Bahasa Inggris, 2013)
This present study aims at investigating the effect of self- assessment and self-concept on studentsÃ¢â¬â¢ writing competancy. To fulfill the porpose of the study 80 students out of 120 eighth grade students of MTs Darul Aitam Jerowaru in academic year 2012/2013 were recruited as the research sample through a simple random sampling to have two new classes thought outside the school schedule which was determined based on studentsÃ¢â¬â¢ self-concept level in studying English. This exprimental study was designed witih a 2x2 factorial design. The instrument used to collect the data were posttest of writing and rubric with a quistionare of selft-concept in studying Engglish. The data were analyzed by using two- way ANOVA. The data shows that there is a significant effect between self-assessment on studentÃ¢â¬â¢ writing competency and there is a significant interactional effect between self-asessment and self-concept on studentÃ¢â¬â¢ writing competency. The analysis shows that there is a significant difference in writing competency between the students with high self-concept assessed by using self-assessment and those assessed by using coventional assessment and the student with low concept also indicates the same result.keyword : Self-assessment, conventional assessment, self-concept and writing competency.